Ảnh hưởng của yếu tố địa lý đến tăng trưởng kinh tế các tỉnh thành Việt Nam - Nguyễn Khắc, Hiếu; Trần Thị Thu, Hà (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study analyzes the impact of geographical factors on regional economic growth in Vietnam. The author use fixed effects model (FEM) and generalized method of moments (GMM) to analyze panel data of 63 provinces from 2010 to 2020. The results show that geographical factors have a significant impact on income per capita. Specifically, river factor and average of temperature have positive effects on income per capita in Vietnam. In contrast, variation of temperature, variation of precipitation, average of precipitation and distance to nearest seaport have a negative impact on income per capita in Vietnam. From the results, some policy implications are proposed for allocating investment capital to take the advantages of geographical factors to develop regional economy.
Keywords: Geography; Climate; Income; Economic growth